Desperate House Sellers: Distress among Developers - van Straelen, Eileen (Review of Financial Studies, 2024)
Abstract I identify the effect of financial constraints on product prices using granular data on home-builder housing developments from the 2006–2009 housing crisis. Builders who experience losses in one area subsequently sell homes in unaffected areas at a discount to raise cash quickly. When builders cut prices, they sell homes faster and builders cut prices more in areas in which price cuts produce larger declines in time-to-sale. Financially constrained firms are more likely to cut prices of homes in healthy areas following losses elsewhere. Firms cut prices following losses in other projects only during the crisis, not during the boom.